'An incredibly vile sport': Campaigns against Otter Hunting in Britain, 1900–39. Issue 1 (3rd March 2016) - ALLEN, DANIEL; WATKINS, CHARLES; MATLESS, DAVID
Abstract: Otter hunting was a minor field sport in Britain but in the early years of the twentieth century a lively campaign to ban it was orchestrated by several individuals and anti-hunting societies. The sport became increasingly popular in the late nineteenth century and the Edwardian period. This paper examines the arguments and methods used in different anti-otter hunting campaigns 1900–1939 by organisations such as the Humanitarian League, the League for the Prohibition of Cruel Sports and the National Association for the Abolition of Cruel Sports.